2017
DOI: 10.22606/jaam.2017.21005
|View full text |Cite
|
Sign up to set email alerts
|

Further Study on Semi-prequasi-invex Type Programming

Abstract: The purpose of this paper is to study semi-prequasi-invex type multiobjective optimization problem with inequality constraints and generalized nonlinear fractional programming. Two alternative theorems and an optimality necessary condition for multiobjective optimization problem are obtained. Moreover, a strong duality theorem and a saddle point theorem for generalized nonlinear fractional programming are derived. Our results improve and generalize the corresponding ones in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Peng [9] proposed a new class of generalized functions G-E-semi-preinvex functions, and obtained the optimality results and Wolfe duality problem for G-E-semi-preinvex multi-objective programming problems. A related study of generalized convexity and optimality of planning problems can be found in the literatures [10][11][12][13][14][15]. These literatures have good implications for the study of generalized convexity.…”
Section: Introductionmentioning
confidence: 99%
“…Peng [9] proposed a new class of generalized functions G-E-semi-preinvex functions, and obtained the optimality results and Wolfe duality problem for G-E-semi-preinvex multi-objective programming problems. A related study of generalized convexity and optimality of planning problems can be found in the literatures [10][11][12][13][14][15]. These literatures have good implications for the study of generalized convexity.…”
Section: Introductionmentioning
confidence: 99%